THE SPONGEBOB MOVIE : SPONGE OUT OF WATER - Tibbitt, Paul; Kenny, Tom 1962-; Banderas, Antonio; Fagerbakke, Bill, 1957-; Conway, Tim; Hillenburg, Stephen; Paramount Animation (Firm); Nickelodeon Movies; United Plankton Pictures; Paramount Pictures Corporation (Hollywood, CA : Paramount Pictures, 2015)
When pirate Burger Beard steals the secret recipe for the beloved Krabby Patties, SpongeBob and friends come ashore to bring back the missing formula. To succeed, they must team up with former rival, Plankton, but soon realize that to defeat a super-villain, they must unleash their inner superheroes.
Title from container.
Based on the series SpongeBob Squarepants created by Stephen Hillenburg.
FEATURE FILM + BONUS FEATURES: Join SpongeBob and friends for 3 EXCLUSIVE SING-ALONG MUSIC VIDEOS ; Dive into their world with 8 EXCITING FEATURETTES that take you from bikini Bottom to the surface ; Come ashore with STORYBOARDS, DELETED SCENES AND MORE.
Edited by David Ian Salter ; music by John Debney.
Tom Kenny, Antonio Banderas, Bill Fagerbakke, Tim Conway.
Rating: PG; for mild action and rude humor. Board of Film Censors, Singapore rating: PG (Parental Guidance)
Keywords: SpongeBob SquarePants -- (Fictitious character); Theft -- Juvenile films; Superheroes -- Juvenile films; Pirates -- Juvenile drama; Outlaws -- Juvenile drama